Overlapping features of restless legs syndrome and growing pains in Turkish children and adolescents - TÜRKDOĞAN, DİLŞAD (My University, 2022)
Background: Restless legs syndrome (RLS) and growing pains (GPs) share many common features and are sometimes overlapping diagnoses. The present study aims to investigate the shared features of patients with RLS, classified based on the 2013 diagnostic criteria of International Restless Legs Syndrome Study group and of patients with GPs, diagnosed based on the combined criteria proposed in 2013.Methods: A cross-sectional population study was conducted in 7 Istanbul schools, which were selected randomly. A total of 4565 (56.1% female) children aged 9 to 18 years were included. In the first stage, candidates of RLS and GPs were identified based on 2 separate questionnaires, whose diagnoses were confirmed by a second survey applied to them under parental supervision.Results: Out of 192 children (65.6% female) diagnosed as definite RLS (yearly prevalence: 4.2%), 30 (15.6%) reported bilateral leg muscle pain localized typical regions for GPs, which started <13 years of age in 17 children. An urge to move the legs to relieve unpleasant sensations or pain was present in 39.3% of 140 children (64.3% female) classified as GPs (yearly prevalence: 3.1%). Occurrence of symptoms at rest or when lying down was present in 36.4% of GPs children and relief by gross movements was in 21.4% children. Only 12 patients (9 with definite RLS and 3 with GPs) (0.03% of total cohort) were eligible for overlapping diagnosisConclusion: Although a considerable number of patients with RLS and GPs share some clinical features, a combined phenotype is very rare. (c) 2022 The Japanese Society of Child Neurology Published by Elsevier B.V. All rights reserved.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Nöroloji; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Neurology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatri; Nöroloji (klinik); Pediatri, Perinatoloji ve Çocuk Sağlığı; Yaşam Bilimleri; Pediatrics; Neurology (clinical); Pediatrics, Perinatology and Child Health; Life Sciences; Restless legs syndrome; Growing pains; Prevalence; Combined diagnostic criteria; Overlapping features; Combined phenotype; DIAGNOSTIC-CRITERIA; PREVALENCE; EPIDEMIOLOGY; CHILDHOOD; SYMPTOMS; UPDATE; Restless legs syndrome; Growing pains; Prevalence; Combined diagnostic criteria; Overlapping features; Combined phenotype